Taxonomic notes and updated phylogeny of the fishfly genus Ctenochauliodes van der Weele (Megaloptera: Corydalidae) - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2011)
Ctenochauliodes khasianus (van der Weele, 1909), comb. nov. is redescribed for the first time after its original description. The identity of Ctenochauliodes nigrovenosus (van der Weele, 1907) is clarified, with C. friedrichi Navás, 1932 treated as a new junior synonym. A species previously listed from China as C. nigrovenosus (van der Weele, 1907), is herein described as a new species, Ctenochauliodes stigmosus sp. nov. A revised key to males of the genus is provided. An updated interspecific phylogeny of Ctenochauliodes is also presented.